2019
DOI: 10.3390/v11090804
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal HAdV Infection: Tissue Specificity, Persistence, and Implications for Antiviral Therapy

Abstract: Human adenovirus (HAdV) causes infections predominantly in early childhood and the tissue tropism of specific HAdV species determines the clinical manifestation, including infections of the gastrointestinal tract, respiratory tract, and keratoconjunctivitis. Why HAdV shows such a tropism has not yet been fully elucidated, but in the intestine different mechanisms for virus entry or resistence to immune modulatory factors have been described. Recently identified antiviral strategies by interferons provide evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 84 publications
0
34
0
Order By: Relevance
“…39 In addition, it is known that specific HAdV species have distinct tissue tropism which may determine the clinical presentation. 40 The presence of HAdV in respiratory tract and stool samples from patients not presenting with any clinical symptoms might be detected incidentally, thus making interpretation of the clinical significance of a positive result difficult. Yet, in our study, samples of the patients who had any clinical presentation associated with HAdV infection were referred for laboratory diagnostics testing to our institute upon the request of the seeing physician when an adenovirus infection was suspected.…”
Section: Dovepressmentioning
confidence: 99%
“…39 In addition, it is known that specific HAdV species have distinct tissue tropism which may determine the clinical presentation. 40 The presence of HAdV in respiratory tract and stool samples from patients not presenting with any clinical symptoms might be detected incidentally, thus making interpretation of the clinical significance of a positive result difficult. Yet, in our study, samples of the patients who had any clinical presentation associated with HAdV infection were referred for laboratory diagnostics testing to our institute upon the request of the seeing physician when an adenovirus infection was suspected.…”
Section: Dovepressmentioning
confidence: 99%
“…See Table 1 for the subtypes of Group B and D HAdV. 11,12 HAdV type 3, 7, and 21 of Group B can cause keratoconjunctivitis, urinary tract infection, respiratory infection, and GIT infection. Group D HAdV can also cause both ocular and GIT infection.…”
Section: Virologymentioning
confidence: 99%
“…17 Additionally, asymptomatic passage of adenovirus in the stool of patients with previous adenoviral GIT infection can also occur. 3,11 Kosulin et al suggested that latent HAdV infection of the gut lymphoid cell could serve as a source of release of HAdV particles in the community. 18 Garnett et al demonstrated the asymptomatic persistence of group C adenovirus in human mucosal T lymphocytes or lymphoid tissue following primary adenoviral infection.…”
Section: Virologymentioning
confidence: 99%
See 1 more Smart Citation
“…Although rarely detected in peripheral blood lymphocytes [150][151][152], adenovirus is frequently found in lymphocytes residing in lymphoid organs of the oropharynx [153][154][155] and intestine [156][157][158]. Adenovirus may persist as a smoldering infection in the intestine from which it can be shed in the feces of asymptomatic individuals [150,159].…”
Section: Epigenetic Alterations In Persistently Infected Cellsmentioning
confidence: 99%